Multivariate Public Key Cryptosystems - Ding, Jintai; Gower, Jason E.; Schmidt, Dieter S.; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
Multivariate public key cryptosystems (MPKC) is a fast-developing new area in cryptography. In the past 10 years, MPKC schemes have increasingly been seen as a possible alternative to number theoretic-based cryptosystems such as RSA, as they are generally more efficient in terms of computational effort. As quantum computers are developed, MPKC will become a necessary alternative. Multivariate Public Key Cryptosystems systematically presents the subject matter for a broad audience. Information security experts in industry can use the book as a guide for understanding what is needed to implement these cryptosystems for practical applications, and researchers in both computer science and mathematics will find this book a good starting point for exploring this new field. It is also suitable as a textbook for advanced-level students. Written more from a computational perspective, the authors provide the necessary mathematical theory behind MPKC; students with some previous exposure to abstract algebra will be well-prepared to read and understand the material. .
Overview -- Matsumoto-Imai Cryptosystems -- Oil-Vinegar Signature Schemes -- Hidden Field Equations -- Internal Perturbation -- Triangular Schemes -- Direct Attacks -- Future Research.
Keywords: Computer science; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computers; Computer science -- Mathematics; Computer Science; Data Encryption; Data Structures, Cryptology and Information Theory; Coding and Information Theory; Data Structures; Mathematics of Computing; Theory of Computation; Electronic books